Architectures of Trust: Open Science between Ivory Tower and Panopticon. - Kallergi, Amalia; Landeweerd, Laurens (NanoEthics, 2025)
Transparency and openness are frequently praised as vital institutional strategies to foster public trust in science. The expectation is that transparent and open science will be more trusted, either because publics will have access to information about what scientists do or because scientists will behave better under the watchful gaze of others. In this contribution, we challenge this widespread assumption by searching for the downsides of transparency in relation to public trust in science. The question we ask is: could transparency also have unintended negative effects on public trust? First, we consider theoretical treatments of transparency that challenge its status as an absolute value. This analysis highlights the benefits of seclusion and secrecy and the perils of excessive transparency. Next, we turn to the practice of transparency, as enacted via open-science strategies. Open Science is a framework defined by a commitment to openness, sharing and collaboration; effectively, it offers a set of actionable strategies for scientists to be transparent. We examine risks associated with both specific open-science strategies and an Open Science normativity. This allows us to explicate three concrete pathways via which the enactment of transparency could inadvertently harm public trust in science. These pathways indicate that transparency (as enacted via open-science strategies) could fuel 1) well-placed distrust, 2) misplaced trust or 3) misplaced distrust. Eventually, we conclude that the architecture of Open Science needs a conditional and contextual operationalisation of transparency which results in new responsibilities for the scientific community.